Energy Poverty in Sub-Saharan African Countries: Harnessing Green Energy for Youth Employability and Economic Transformation - Oluwatayo, Isaac B. (International Journal of Energy Economics and Policy, 2026)
Energy poverty remains a critical developmental challenge across sub-Saharan African (SSA) countries, where over 600 million people lack access to reliable, affordable, and sustainable electricity. This persistent energy deficit impedes socioeconomic progress, limits educational and health outcomes, and stifles industrialization and entrepreneurship. Youth, who constitute more than 60% of the region’s population, are disproportionately affected, facing high unemployment rates and limited opportunities for meaningful engagement in the formal economy. This paper explores the intersection of energy poverty and youth employability, emphasizing the transformative potential of harnessing green energy to drive inclusive economic development. Green energy comprising solar, wind, biomass, hydro, and geothermal sources offers a scalable and sustainable solution to SSA’s energy crisis. It presents an opportunity not only to expand energy access but also to create jobs, stimulate innovation, and foster entrepreneurship among youth. Through decentralized renewable energy systems such as mini-grids and solar home systems, rural and off-grid communities can be empowered to participate in local economies, enhancing resilience and reducing rural-urban drifts.